PROSES MEMFASILITASI BELAJAR DAN MENINGKATKAN KINERJA GURU DAN SISWA PADA PENDIDIKAN AGAMA ISLAM KELAS V DI SEKOLAH DASAR NEGERI NO 189/VI PINANG MERAH II - Aini, Roslina; Hadi, Ahmad Syarpul; Hasian, Radi; Rusdi, Gempa; Nuzli, Muhammad (Institut Agama Islam Syekh Maulana Qori Bangko, 2022)
This study aims to determine the process of facilitating the achievement of learning objectives of Class V Islamic Religious Education at SD Negri 189/VI Pinang Merah II, besides that it also wants to know the facilities used to improve student achievement by increasing student performance in learning Islamic Religious Education. This research was conducted using a qualitative approach, data was collected to find out this information by using observation to observe the learning process of Islamic Religious Education, interview methods to obtain information from Students and Teachers of Islamic Religious Education and other sources. The results of research conducted to achieve optimal teacher performance have attempted to develop and create situations in the school environment in accordance with applicable regulations, so as to create a generation that is intelligent and able to answer the challenges that will come in the future.